A review paper of: the impact of daylight on students‟ learning performance - A. Samani, Sanaz.; A. Samani , Soodeh.; Parasteh, Masoud (Journal of Management and Science, 2013)
The purpose of this study is to identify the impact of daylight on students‘ learning performance within learning environments. Since, learning plays an important role in people‘s life; having suitable and appropriate learning place seems very important an essential. It can motivate people to learn more and better. Learning environment includes all schools, universities or other places even libraries where people study there. Well designed learning palaces make students happy and energize and vice versa. In general, lighting in an environment is one of the necessary and important elements which have direct impact on people‘s performance. Apart from all indoor (artificial) light profits, natural light itself has more benefits on peoples‘ health and wellbeing. Having apt windows in classrooms are very important for having appropriate daylight, and also outside viewing. This connection with outside can provide significant physical and physiological benefits for users especially students. In this study the researchers try to identify the importance of daylight in learning places and discover the influence of that on students‘ learning performance. The result that comes from this study indicates that applying daylight in learning environment is very essential, but students feel and understand that while they involved with that. This paper is a review paper which came for a master thesis. Researchers review that to find support for the hypothesis that applying daylight in classrooms affects and enhances students‘ learning performance.